An epigenome-wide association study of inflammatory response to fenofibrate in the Genetics of Lipid Lowering Drugs and Diet Network. (September 2017) - Yusuf, Nabiha; Hidalgo, Bertha; Irvin, Marguerite R; Sha, Jin; Zhi, Degui; Tiwari, Hemant K; Absher, Devin; Arnett, Donna K; Aslibekyan, Stella W
Aim: Fenofibrate, a PPAR-α inhibitor used for treating dyslipidemia, has well-documented anti-inflammatory effects that vary between individuals. While DNA sequence variation explains some of the observed variability in response, epigenetic patterns present another promising avenue of inquiry due to the biological links between the PPAR-α pathway, homocysteine and S -adenosylmethionine – a source of methyl groups for the DNA methylation reaction.Hypothesis: DNA methylation variation at baseline is associated with the inflammatory response to a short-term fenofibrate treatment.Methods: We have conducted the first epigenome-wide study of inflammatory response to daily treatment with 160 mg of micronized fenofibrate over a 3-week period in the Genetics of Lipid Lowering Drugs and Diet Network (GOLDN, n = 750). Epigenome-wide DNA methylation was quantified on CD4 + T cells using the Illumina Infinium HumanMethylation450 array.Results: We identified multiple CpG sites significantly associated with the changes in plasma concentrations of inflammatory cytokines such as high sensitivity CRP (hsCRP, 7 CpG sites), IL-2 soluble receptor (IL-2sR, one CpG site), and IL-6 (4 CpG sites). Top CpG sites mapped to KIAA1324L (p = 2.63E-10), SMPD3 (p = 2.14E-08), SYNPO2 (p = 5.00E-08), ILF3 (p = 1.04E-07), PRR3, GNL1 (p = 6.80E-09), FAM50B (p = 3.19E-08), RPTOR (p = 9.79e-07) and several intergenic regions (p < 1.03E-07). We also derived two inflammatory patterns using principal component analysis and uncovered additional epigenetic hits for each pattern before and after fenofibrate treatment.Conclusion: Our study provides preliminary evidence of a relationship between DNA methylation and inflammatory response to fenofibrate treatment.